Breaking behaviour of long grain brown rice - Suteera Prasertsan (Prince of Songkla Univ., Hat Yai (Thailand). Dept. of Mechanical Engineering) (2013)
Long grain brown rice was tested on a universal testing machine. The experiments were longitudinal tension and compression and lateral compressive and cyclic loadings. The fractography of tension test revealed that the broken surface comprised of many radially-oriented-small ruptured areas and the breaking mechanism was shear failure. Burstout in radial direction was found in the longitudinal compression test and was explainable. The cohesive force of the rice kernel was not isotropic. The kernel was relatively weak under transverse tensile strain. Cyclic loading test established a critical cylic load. Force and breaking cycles exhibited an exponential relationship